From Efficacy to Effectiveness of a "Whole Child" Initiative of Physical Activity Promotion. Issue 3 (1st May 2016) - Pesce, Caterina; Leone, Liliana; Motta, Anna; Marchetti, Rosalba; Tomporowski, Phillip D.
Abstract : ABSTRACT: After the call for more translational studies documenting physical activity intervention via the reach, effectiveness, adoption, implementation, and maintenance (RE-AIM) framework, this study aimed to evaluate a school-based corporate social responsibility initiative of "whole child" development promotion through physical activity centered on deliberate play. In accordance with our holistic intervention approach, we performed a comprehensive evaluation integrating the use of the RE-AIM framework for translational health promotion research and an evaluation framework for school-based programs of positive youth development with emphasis on ecological validity. The intervention reached almost 40% of the target children's population, with effects differing in size in multiple domains, leading to a composite reach–effectiveness index of 0.14. Adoption was total (100%) at the setting level and 50% at the school staff level, but it weakened because of the school teacher's low attendance in staff training (40% participated in >50% of the teacher training). This, together with a good consistency adaptation trade-off set point due to a systematic monitoring of implementation fidelity, led to a composite adoption–implementation index of 0.16. The average number of classes involved (maintenance) after randomized controlled trial completion was larger than that at the beginning of the randomized controlled trial (125%). In conclusion, a quality physical activity program grounded on a child's right to play and targeted to holistic child development involves multiple foci and complex implementation by multiple actors from public and private sectors. Our integrated use of the RE-AIM framework and that for positive youth development programs seems a suitable approach for a comprehensive, multidimensional evaluation of strengths and limitations of such kind of positively framed investment on physical activity for personal and social change.